Left Atrial Function in Young Patients With Cryptogenic Stroke and Patent Foramen Ovale: A Left Atrial Longitudinal Strain Study - Gazagnes, Julie; Gollion, Cédric; Fournier, Pauline; Cariou, Eve; Larrue, Vincent; Lairez, Olivier (Frontiers in Neurology, 2020)
Background – The study of left atrial (LA) longitudinal strain by speckle tracking is a reliable method for analyzing LA function that could provide relevant information in young patients with cryptogenic stroke (CS). The aim of this study was to investigate whether the presence of a patent foramen ovale (PFO) impacts the LA longitudinal strain in a population of young patients with first CS. Methods and Results – Patients aged 18 to 54 years, treated consecutively in a university hospital for first CS, were included in this study. The presence of a PFO and an atrial septal aneurysm (ASA) was investigated using transesophageal echocardiography and transcranial Doppler. Speckle tracking analysis was performed on transthoracic echocardiography, allowing the measurement of global, passive and active longitudinal LA strain, corresponding to the reservoir, conduit, and contractile function, respectively. A total of 51 patients were included in the study. Global longitudinal LA strain was significantly reduced in older (>44 years) patients (P=0.009), and in the presence of hypertension (P=0.002) and overweight (P=0.001). Passive longitudinal LA strain was also reduced in older (P<0.001), and overweight patients (P=0.004). LA function was not different between patients with PFO or PFO plus ASA and patients without. Conclusion – LA longitudinal strain in young subjects with CS was impaired in older patients, and in the presence of hypertension or overweight, but not of PFO or PFO plus ASA